Pemanfaatan Limbah Cangkang Kerang Mutiara (Pinctada Maxima) Sebagai Sumber Hidroksiapatit - Susi Rahayu; Dian W Kurniawidi; Abdul Gani (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
Pearl shells (pinctada maxima) are the superior commodities in West Nusa Tenggara Province. The shellfish is utilized as a producer of pearls while the waste of pearl shells has not been widely used by the community. Main composition of fhe pearl shells is calcium. CaO content was tested using AAS and obtained CaO in shells as much as 52.23%. CaO is used as a source of hydroxyapatite (HAp). Shellfish powder is synthesized with H3PO4 compound. Synthesis is conducted by precipitation method. Synthesis results were analyzed utilizing XRD and FTIR. From the examination, HAp compounds were identified. Group of PO43, CO32, and OH are constituent groups of HAp compounds. Moreover, another calcium phosphate is formedÃÂ  namely TCP. This HAp compound has a maximum crystallinity of 78.33% at an angle of 77.18 ÃÂ°. The smallest HAp particle size at an angle of 31.92 ÃÂ° is 1.4 ÃÂ¼m. The degree of high crystallinity is influenced by high intensity and a wide FWHM. Meanwhile, the small molecule size is acquired on a wide FWHM with a small Bragg angle position.